PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA DAN EDUCAPLAY PADA MATERI LUAS BANGUN DATAR KELAS V SEKOLAH DASAR - Nurhasni; Refiona Andika; Yarisda Ningsih; Fadilah Suciana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the fact that the use of interactive learning media based on Canva and Educaplay applications in fifth-grade elementary schools has not been maximized, and the learning process still does not utilize technological developments. Most of the learning is explained using conventional learning media. The purpose of this study was to develop interactive learning media based on Canva and Educaplay applications on area of flat shapes material in fifth grade that are valid, practical, and effective in fifth-grade elementary school. This research uses Research and Development (R&D) method with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The practicality test subjects were fifth-grade students of SDN 003 Pebaun Hulu and SDN 015 Pebaun Hilir, while the effectiveness test was conducted at SDN 004 Sungai Manau. Data collection instruments included expert validation sheets (material, media, and language), teacher and student response questionnaires, as well as pre-test and post-test. Data analysis techniques used percentages for validity and practicality, and the N-Gain test for effectiveness. The results showed that the developed interactive learning media was declared very valid with a percentage of 97.3% from material experts, 92.8% from media experts, and 94% from language experts. Practicality test results showed a very practical category based on teacher responses (95.83%–100%) and student responses (89.7%–98.21%). The effectiveness test results obtained an N-Gain value of 0.710475 with a